Revolutionising education: In the midst of the COVID-19 crisis and its global implications, China pioneers online learning strategies - Ming Lojunt; Shanshan lie lie; Fangmei Li Li (Advances Educational Innovation, 2024)
Objective: This study investigates the effectiveness and global implications of China's innovative online education strategies implemented during the COVID-19 pandemic, with a focus on academic performance, engagement, and equity in learning outcomes.Methods: A quasi-experimental design was employed, utilizing data from 700 undergraduate students in Wuhan, China, collected from 2019 to 2024. Statistical analyses, including paired t-tests and regression models, were conducted to evaluate differences in academic performance across demographic groups and assess the correlation between engagement levels and learning outcomes.Results: The findings revealed that China's large-scale online education initiatives significantly enhanced academic performance and engagement, especially among urban students. However, challenges such as the digital divide persisted, disproportionately affecting rural learners. These insights emphasize the importance of equitable resource distribution in online education.Novelty: This research provides a unique perspective on the rapid adaptation of educational systems during a global crisis, highlighting China's unprecedented efforts to maintain learning continuity. It identifies both strengths and limitations of large-scale online learning, offering innovative solutions for bridging gaps in digital education.Theory and Policy Implications: The results validate key theoretical frameworks, including the Technology Acceptance Model and Engagement Theory, while providing actionable recommendations for policymakers. These include strategies for enhancing digital infrastructure, improving accessibility, and fostering sustainable online education models globally